Beyond Arabidopsis: Differential UV-B Response Mediated by UVR8 in Diverse Species - Tossi, Vanesa Eleonora; Regalado, Jose Javier; Iannicelli, Jesica; Laino, Leandro Ezequiel; Burrieza, Hernan Pablo; Escandón, Alejandro Salvio; Pitta-Álvarez, Sandra Irene (Frontiers in Plant Science, 2019)
Ultraviolet-B radiation (UV-B, 280–315 nm) is an important environmental signal that regulates growth and development in plants. Two dose-dependent UV-B response pathways were described in plants: a specific one, mediated by UVR8 (the specific UV-B receptor) and an unspecific one, activated by the oxidative damage produced by radiation. The constitutively expressed receptor appears inactive as a dimer, with the two monomers dissociating upon UV-B irradiation. The monomer then interacts with COP1, an ubiquitin ligase, hindering its ability to poly-ubiquitinate transcriptional factor HY5, thus averting its degradation and activating the photomorphogenic response. HY5 induces the synthesis of proteins RUP1 and RUP2, which interact with UVR8, releasing COP1, and inducing the re-dimerization of UVR8. This mechanism has been thoroughly characterized in Arabidopsis, where studies have demonstrated that the UVR8 receptor is key in UV-B response. Although Arabidopsis importance as a model plant many mechanisms described in this specie differ in other plants. In this paper, we review the latest information regarding UV-B response mediated by UVR8 in different species, focusing on the differences reported compared to Arabidopsis. For instance, UVR8 is not only induced by UV-B but also by other agents that are expressed differentially in diverse tissues. Also, in some of the species analyzed, proteins with low homology to RUP1 and RUP2 were detected. We also discuss how UVR8 is involved in other developmental and stress processes unrelated to UV-B. We conclude that the receptor is highly versatile, showing differences among species.